Bis{2-[(E)-benzyliminomethyl]-4,6-dibromophenolato-κ(2) N,O}cobalt(II) - Jiang, Wei (International Union of Crystallography, 2008)
In the title compound, [Co(C(14)H(10)Br(2)NO)(2)], the Co(II) ion is coordinated by an O and an N atom from two equivalent 2-[(E)-benzyliminomethyl]-4,6-dibromophenolate ligands, displaying a distorted tetrahedral geometry. The Co(II) ion occupies a special position on a twofold rotation axis and thus the molecular symmetry of the complex is C (2). The two phenolate rings are perpendicular [89.8 (3)°].